The incidence of invasive pneumococcal serotype 3 disease in the Danish population is not reduced by PCV-13 vaccination. Issue 11 (November 2016) - Slotved, Hans-Christian; Dalby, Tine; Harboe, Zitta Barrella; Valentiner-Branth, Palle; Casadevante, Victoria Fernandez de; Espenhain, Laura; Fuursted, Kurt; Konradsen, Helle Bossen
Abstract: Since 2010, Denmark has included the 13-valent pneumococcal conjugated vaccine (PCV-13) in the childhood immunization programme. However, serotype 3 remains as an important cause of invasive pneumococcal disease (IPD) in Denmark. IPD surveillance data (1999–2016) was used to calculate the incidence and age-distribution of serotype 3 IPD, and the effect of PCV-13 on serotype 3 IPD incidence was examined. The incidence of serotype 3 IPD in the age group below 65 years was 0.51/100, 000 pre PCV-13, and 0.45/100, 000 post PCV-13. In the group 0–4 years, serotype 3 IPD incidence was 0.28/100, 000 pre PCV-13, and 0.16/100, 000 post PCV-13. Serotype 3 IPD incidence in the elderly showed a mean of 4.27/100, 000 pre PCV-13, and 4.32/100, 000 post PCV-13. PCV-13 childhood immunization in Denmark has not lead to a reduction of the incidence of IPD caused by serotype 3. The reason behind this missing effect needs to be investigated further.